Effect of socio-economic status and estimation of lipid peroxidation and antioxidant in preeclamptic pregnant women: a case–control study. (February 2015) - Sarwar, Md. Shahid; Sarkar, Rakhesh Chandra; Bhowmick, Rumpa; Dewan, Syed Masudur Rahman; Ahmed, Maizbha Uddin; Hasnat, Abul; Rashid, Mamunur; Islam, Mohammad Safiqul
<x xml:space="preserve">Abstract</x> Objective: Increased extent of lipid peroxidation and decreased antioxidant defense has been postulated as a major contributor to the development of preeclampsia. The present study was conducted to determine the serum level of malondialdehyde (MDA) and vitamin C in these patients. Methods: This research was conducted as a case–control study to assess the extent of lipid peroxidation and antioxidant status in 150 preeclampsia patients and 174 healthy pregnant women. Lipid peroxidation was assessed by measuring serum MDA level, and antioxidant defense was evaluated for serum vitamin C by UV spectrophotometric method. Independent sample t test and Pearson's correlation test were used for the statistical analysis with statistical software package SPSS, version 16.0 (SPSS, Inc., Chicago, IL). Results: Our study found significantly higher level of MDA (p < 0.05) and significantly lower level of vitamin C (p < 0.05) in preeclampsia patients in comparison to the control subjects. Pearson's correlation analysis revealed that there was negative correlation between the serum level of MDA and vitamin C for both patient (r = −0.057, p = 0.669) and control groups (r = −0.128, p = 0.487). Analysis of socio-economic data revealed that preeclampsia was more prevalent among the rural pregnant than the urban pregnant women (OR 1.44, 95% CI 0.665–3.14, p = 0.352). It was also observed that primigravida pregnant were at higher risk for the development of preeclampsia than the multigravida pregnant women (OR 1.87, 95% CI 0.868–4.04, p = 0.108). Conclusions: Elevated serum MDA and depleted serum vitamin C may be associated with the development of preeclampsia.